Do Capital Flows Respond to Risk and Return? - Calderon, Cesar; Loayza, Norman; Serven, Luis (World Bank, Washington, DC, 2014)
This paper explores empirically the role of risk and return in the observed evolution of net foreign asset positions of industrial and developing economies. The paper adopts a dynamic approach in which investors' portfolios adjust gradually to their long-run equilibrium, defined by a standard Tobin-Markowitz framework. The parameters characterizing the long-run equilibrium are estimated using data on foreign assets and liabilities of a large number of industrial and developing countries spanning the period from 1965 to 1997. The paper employs a dynamic panel estimation procedure allowing for unrestricted short-run heterogeneity across countries, using the pooled mean group estimator recently developed by Pesaran, Shin, and Smith (1999). The empirical results lend considerable support to the model when applied to countries with low capital controls and/or high and upper-middle income. The results for countries with either high capital controls or low per capita income are less supportive of the stock equilibrium model for net foreign asset positions.